2014
DOI: 10.1371/journal.pone.0099383
|View full text |Cite|
|
Sign up to set email alerts
|

Uncoupling between Inflammatory and Fibrotic Responses to Silica: Evidence from MyD88 Knockout Mice

Abstract: The exact implication of innate immunity in granuloma formation and irreversible lung fibrosis remains to be determined. In this study, we examined the lung inflammatory and fibrotic responses to silica in MyD88-knockout (KO) mice. In comparison to wild-type (WT) mice, we found that MyD88-KO animals developed attenuated lung inflammation, neutrophil accumulation and IL-1β release in response to silica. Granuloma formation was also less pronounced in MyD88-KO mice after silica. This limited inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 67 publications
4
38
0
Order By: Relevance
“…Indeed, we recently showed that mice lacking IL-1β, IL-1α or IL-1R and treated with DQ12 silica presented a reduction of chronic lung inflammation and granuloma formation compared to their WT counterparts. However, this strong effect on inflammatory development was not concomitantly accompanied by a reduction of lung fibrosis, suggesting that inhibiting IL-1-driven inflammation may not be sufficient to control the fibrotic lung disease after particle exposure [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we recently showed that mice lacking IL-1β, IL-1α or IL-1R and treated with DQ12 silica presented a reduction of chronic lung inflammation and granuloma formation compared to their WT counterparts. However, this strong effect on inflammatory development was not concomitantly accompanied by a reduction of lung fibrosis, suggesting that inhibiting IL-1-driven inflammation may not be sufficient to control the fibrotic lung disease after particle exposure [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…52 Moreover, in a study of the lung inflammatory and fibrotic responses to silica of MyD88 knock-out mice, robust collagen accumulation was observed in knock-out mice in spite of attenuation of lung inflammation, neutrophil accumulation and IL-1β release in response to silica. 62 In that same study, fibrosis was associated with increased levels of pro-fibrotic regulatory T lymphocytes but not with T helper 17 cell influx. 62 The data suggest that the development of lung fibrosis or even other fibrotic diseases appears uncoupled from inflammation and may be orchestrated by a regulatory T lymphocyte-associated pathway.…”
Section: Er Stress Crohn's Disease Intestinal Inflammation and Immumentioning
confidence: 90%
“…62 In that same study, fibrosis was associated with increased levels of pro-fibrotic regulatory T lymphocytes but not with T helper 17 cell influx. 62 The data suggest that the development of lung fibrosis or even other fibrotic diseases appears uncoupled from inflammation and may be orchestrated by a regulatory T lymphocyte-associated pathway. 62 Several ER modulating therapeutic interventions showed that treatment with chemical chaperones improves protein folding in disorders of misfolded proteins, such as alpha-1 antitrypsin deficiency.…”
Section: Er Stress Crohn's Disease Intestinal Inflammation and Immumentioning
confidence: 90%
See 1 more Smart Citation
“…Interest reports to reveal importance of MyoD88 for lung fibrosis and inflammation caused by silica using MyD88 knockout mice were studied by Re et al [64]. They found that accumulation of Treg and cytokines such as IL-10, TGF-β1, and platelet-derived growth factor (PDGF)-B contributed to lung inflammatory and granuloma responses, whereas this was not with Th17 influx.…”
Section: Effects Of Silica Particles and Asbestos Fibers On Th17mentioning
confidence: 99%